Effect of Foliar Liquid Organic Fertilizer to Increase Coconut Neera Production - Purwanto, Purwanto; Mujiono, Mujiono; Tarjoko, Tarjoko (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
Coconut plant is the important estate plant to produce brown sugar from neera. Current condition, the neera production is low especially in dry season. The aim of this research was to study the effect of foliar liquid organic fertilizer to increase the coconut neera production in Kebumen Regency. This research was conducted in Coconut People’s Plantation Karanggadung Village PetanahanKebumen from Juli till October 2016. Randomized Completely block design with factorial treatments was used with 3 replications. The first factors was the dosage of liquid foliar fertilizer solution ie 250 mL plant-1 (d1), 500 mL plant-1 (d2), 750 mL plant-1 (d3), and 1000 mL plant-1 (d4). The second factor is interval time of application ie. 1 week (f1), 2 weeks (f2), 3 weeks (f3), and 4 weeks (f4). The observed variables were volume of neera production, pH of neera, sucrosa content, and leaf chlorophyll contents. The result showed that Application of foliar liquid organic fertilizer increase the leaf greenness at 80.55 SPAD unit at three weeks time interval, as reflected the total chlorophyll content. Fertilization of coconut plant with foliar liquid organic fertilizer increase the neera production about 15,32%, and the highest volume of neera was achieved at the dosage of foliar liquid organic fertilizer 750 mL plant-1 with the frequency of application three weeks.